Human papillomavirus and gastrointestinal cancer in Iranian population: A systematic review and meta-analysis - Versa Omrani-Nava; Reza Alizadeh-Navaei; Yousef Yahyapour; Akbar Hedayatizadeh-Omran; Saeid Abediankenari; Ghasem Janbabaei; Fatima Toghani (Babol University of Medical Sciences, 2017)
Background: Gastrointestinal (GI) malignancies are the most common cancers and account for nearly half of all cancer-related deaths in Iran. There was a strong association between human papillomavirus (HPV) infection and urogenital cancers, in particular the cervix. However, there is no clear causal relationship in all types of cancers, including gastrointestinal cancers. Therefore, the present study as a systematic review and meta-analysis was designed to evaluate the prevalence and relation of HPV in GI cancers. Methods: This systematic review and meta-analysis study assess the prevalence of human papillomavirus in GI cancers in Iran. Data were collected by searching electronic databases, including PubMed, Google Scholar, Scopus, SID and Iranmedex by English and Persian key words up to August 2016. Key words included: Human Papillomavirus, HPV, Cancer, Neoplasm, Carcinoma, Esophageal, colorectal, Gastrointestinal and Iran articles were entered in the EndNote software and duplicate papers were excluded.  Data were extracted and analyzed by comprehensive meta-analysis software, Version 2 (CMA.V2) and random effects model. Results: Finally, we included 17 studies in this meta-analysis. The prevalence of HPV in Iranian patients with GI cancers was 16.4% (CI95%: 10.4-24.9). Considering all HPV types, the odds ratio of GI cancers in positive patients was 3.03 (CI95%: 1.42-6.45) while in patients with HPV-16 was 3.62 (CI: 1.43-4.82). Conclusion: The results show a strong relationship between HPV infection especially high-risk HPV type 16 and GI cancers in Iranian population.